TREATMENT OPTIMISATION OF HEART FAILURE IN PATIENTS WITH ACUTE MYOCARDIAL INFARCTION AND CONCOMITANT TYPE 2 DIABETES MELLITUS - Spivak, Yu.A.; Potyazhenko, M.M.; Lyulka, N.O.; Vakulenko, K.Ye.; Nos, Ya.V. (World of Medicine and Biology, 2022)
The course and consequences of acute myocardial infarction define concomitant diseases, particularly type 2 diabetes mellitus. The primary purpose was to estimate the efficiency of eplerenone in treating heart failure in patients with acute myocardial infarction and type 2 diabetes mellitus. Two groups and two subgroups were formed. Patients underwent general clinical examinations, troponin I, brain natriuretic peptide, and glycosylated hemoglobin. It was found that patients with myocardial infarction and type 2 diabetes mellitus have a significantly higher brain natriuretic peptide level in the blood. In using an optimized treatment scheme, a decrease in the level of the natriuretic peptide was noted in patients without diabetes during the third visit compared to the first and second. Significant differences in brain natriuretic peptide concentrations at different patient visits were found in patients with comorbidities (р=0.037). The appointment of eplerenone to standard therapy for patients with myocardial infarction with and without comorbid pathology has a positive effect on the efficiency of treatment and the course of heart failure, which is confirmed by a decrease in brain natriuretic peptide as one of the leading indicators of the effectiveness of treatment of heart failure progression.
Keywords: acute myocardial infarction; type 2 diabetes mellitus; heart failure; brain natriuretic peptide; eplerenone